On some Aspects of Biology of Itiiome lassula Bodges (Cosmopterygidae)-a Microlepidopteran Pest Introduced to Indira with the Host Leucaena leucocephala (LAM.) De Wit. - Madhavan Pillai, S. R.; Thakur, M. L. (Indian Forester, 1990)
Itiiome lassula the microlepidopteran infesting inflorescence of Su-babul is recorded for the first time from India. Brief account of the pest, damage caused, the life cycle and seasonal incidence of the pest are presented. Impact of its entry to India discussed.